Anthropometry of arm: nutritional risk indicator in amyotrophic lateral sclerosis - Cristina Cleide dos Santos Salvioni; Patricia Stanich; Acary Souza Bulle Oliveira; Marco Orsini (MDPI AG, 2015)
The aim of the paper is to examine the correlation between clinical data, nutritional, respiratory and functional parameters in amyotrophic lateral sclerosis (ALS). This is a descriptive study of 111 ALS patients [91 spinal onset (GS) and 20 bulbar onset (GB)] carried on using nutritional and respiratory parameters and amyotrophic lateral sclerosis functional rating scale (ALSFRS). ALSFRS was analyzed in the main domains (D1, D2 and D3). Forced vital capacity and anthropometric measurements, there was significant association for GS and GB, and in GS there was positive correlation with midarm circumference (MAC) (r=0.30; P=0.020), midarm muscle circumference (r=0.29; P=0.026), arm muscle area (r=0.28; P=0.033) and protein-caloric malnutrition score (r=0.27; P=0.039), while for GB only with body weight (r=0.64; P=0.024). On correlation of nutritional parameters and ALSFRS for GS patients we observed that MAC and %MAC presented positive association with both issues of D1 and D2. For GB, the total score in addition to correlate positively with anthropometric parameters related to lean body mass also presented negative association with a parameter associated with body fat. In summary, it is suggested that the application of anthropometry of arm could be useful in routine monitoring of ALS patients.